A multi-omics approach identifies candidate biomarkers predictive of boar cryotolerance and conception rate - Mills, Kayla; Minton, Amanda; Berndtson, Jodi; Willenburg, Kilby; Ferreira, Christina R. (Frontiers in Animal Science, 2025)
IntroductionThe swine industry underutilizes cryopreserved boar semen due to poor post-thaw viability and variable fertility outcomes. Current semen evaluation methods are retrospective and insufficient for selecting cryotolerant and fertile sires. The aim of this study was to evaluate multiple reaction monitoring (MRM) profiling as a tool for predicting semen cryotolerance and fertility outcomes.MethodsLipidomic and metabolomic analyses using MRM profiling were applied to fresh and post-thaw ejaculates from 16 commercial Duroc boars with known conception rates (CR) from single-sire matings to identify candidate biomarkers predictive of field CR, post-thaw motility loss, and to determine whether CR markers identified in fresh semen persist post-thaw. Boars were classified by their cryotolerance delta score (CDS), which was calculated as the absolute change in motility between arrival at the cryopreservation laboratory and post-thaw, relative to the average loss in motility (low vs. high), and by field CR (low: 75–79%; mid: 80–89%; high: 90–95%).ResultsDistinct lipid and metabolite profiles were associated with each phenotype, revealing 20 candidate markers with an AUC ≥ 0.800 (P < 0.05). Markers predictive of higher post-thaw motility loss included compounds producing MRMs tentatively attributed to saturated long-chain fatty acids and elevated metabolites such as kynurenine (AUC = 0.905). MRMs predictive of < 80% CR were attributed to elevated guanosine (AUC = 0.850) and olealdehyde (AUC = 0.815), whereas > 80% CR showed higher abundance of TG(45:4) (AUC = 0.967) and creatine (AUC = 0.800). Candidate markers for CR were distinct from those associated with motility loss and remained detectable in post-thaw samples.DiscussionThese findings demonstrate that CR and post-thaw motility loss are governed by independent molecular traits and support the development of a multidimensional biomarker-based screening strategy to enhance fertility postthaw. This approach could enable AI centers to improve boar selection and cryopreservation outcomes, ultimately increasing the utility of frozen semen in swine breeding programs.